2005
DOI: 10.4269/ajtmh.2005.72.443
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Leprosy Using Rifampicin as Chemoprophylaxis

Abstract: An intervention study was implemented on five Indonesian islands highly endemic for leprosy to determine whether rifampicin can be used as chemoprophylaxis to prevent leprosy. The population was actively screened before the intervention and subsequently once a year for three years. In the control group, no chemoprophylaxis was given. In the contact group, chemoprophylaxis was only given to contacts of leprosy patients and in the blanket group to all eligible persons. The cohort consisted of 3,965 persons. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 13 publications
0
50
0
Order By: Relevance
“…8 9 Recently an unblinded study on five Indonesian islands used two doses of rifampicin, given with an interval of about 3.5 months. 10 Three populations were compared: a "blanket group" consisting of the population of three small islands on which prophylaxis was given to all eligible people, a "contact group" consisting of the population of one island on which prophylaxis was given only to contacts living in the same household or less than 50 m away, and a "control group" consisting of the population of another island on which no prophylaxis was given. In the blanket group, chemoprophylaxis was associated with a 74.6% reduction in incidence of leprosy, at least during the three years after implementation.…”
Section: Introductionmentioning
confidence: 99%
“…8 9 Recently an unblinded study on five Indonesian islands used two doses of rifampicin, given with an interval of about 3.5 months. 10 Three populations were compared: a "blanket group" consisting of the population of three small islands on which prophylaxis was given to all eligible people, a "contact group" consisting of the population of one island on which prophylaxis was given only to contacts living in the same household or less than 50 m away, and a "control group" consisting of the population of another island on which no prophylaxis was given. In the blanket group, chemoprophylaxis was associated with a 74.6% reduction in incidence of leprosy, at least during the three years after implementation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, RMP is an effective prophylactic agent against leprosy, which remains endemic in many Pacific countries, presumably through clearance of nasal carriage. 17 As mentioned above, mass prophylactic treatment for leprosy was undertaken in Kiribati in the 1990s, with very high rates of community participation of over 90%. 9 Providing anti-tuberculosis treatment to the whole population could in theory eliminate TB in an island nation such as Kiribati, without any other public health actions and without improved diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the heralded COLEP trial, which was conducted on approximately 20,000 contacts of new cases in north-west Bangladesh, showed a protective effect associated with single-dose rifampicin (RIF) treatment of 57% in household and other contacts (Moet et al 2008a). An earlier Indonesian study found that RIF treatment had a significant effect in communities where all individuals were provided prophylaxis, but no effect in communities where only household contacts and direct neighbours were provided RIF prophylaxis (Bakker et al 2005, Moet et al 2008b). These findings were consistent with dapsone prophylaxis programs, which were also more effective when given as a blanket treatment to affected communities .…”
Section: Resultsmentioning
confidence: 99%
“…Various chemoprophylaxis trials have been conducted to determine whether pre-emptive "treatment" can interrupt leprosy transmission and reduce disease prevalence. These studies have demonstrated a significant benefit to treating non-diseased individuals, although each has reported a different magnitude and length of protection (Daulako 1999, Tin 1999, Diletto et al 2000, Nguyen et al 2000, Vijayakumaran et al 2000, Moet et al 2004, Bakker et al 2005, Smith 2008). The findings of the heralded COLEP trial, which was conducted on approximately 20,000 contacts of new cases in north-west Bangladesh, showed a protective effect associated with single-dose rifampicin (RIF) treatment of 57% in household and other contacts (Moet et al 2008a).…”
Section: Resultsmentioning
confidence: 99%